My Photos for Mac - Grothaus, Michael (Que, 2015)
COVERS Photos for OS X® Yosemite 10.10.3 and higher. Step-by-step instructions with callouts to Photos screenshots that show you exactly what to do. Help when you run into problems with Photos. Tips and Notes to help you get the most from Photos. Full-color, step-by-step tasks walk you through doing everything you want to do with Photos for Mac. Learn how to: Import your photos from digital cameras, iPhones®, iPads®, and more Navigate your photos by Years, Collections, and Moments Search your photos by description, date, location, and more Organize your photos into albums Create Smart albums Create Faces collections to group photos of your friends and family together Store all your photos and videos in iCloud Photo Library Enhance and retouch your photos Add effects and filters to your photos Use Photos' advanced editing tools Create printed books, cards, and calendars using your photos Create slideshows Share your photos online via iCloud, Facebook, Flickr, Twitter, and more.